Optimization of Vibro-Seismic Parameters for Enhanced Oil Recovery Application - Abdel Aal, Tarek (AUC Knowledge Fountain, 2024)
This thesis was conducted in the American University in Cairo by Tarek Ahmed Abdel Fattah Abdel Aal. The thesis is titled ‘Optimization of Vibroseismic Parameters for Enhanced Oil Recovery Application.’ The thesis discusses whether or not the combination of optimized physical vibration parameters with waterflooding would improve porosity, absolute permeability, relative permeability, and recovery when compared with just classical waterflooding. The optimized physical vibration parameters as well as methodology was used from a previous paper that was performed in conjunction with my thesis advisor on similar core samples. The experimentation was performed on five core samples with different porosities and absolute permeabilities. The original porosity, absolute permeability, relative permeability, and recovery which represents the classical waterflooding on its own were measured. These properties were then re-measured after the optimized physical vibration and waterflooding were performed. It was found that the coupling of optimized physical vibration parameters with waterflooding does improve all aspects of the core tested when compared with classical waterflooding.